2018
DOI: 10.1002/hep4.1155
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease contributes to subclinical atherosclerosis: A systematic review and meta‐analysis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is associated with an increased risk of atherosclerotic cardiovascular disease. In our meta‐analysis, we aimed to assess the correlation of NAFLD and four surrogate markers of subclinical atherosclerosis. PubMed, Embase, and the Cochrane Library were searched up until April 2017. Original studies investigating the association between NAFLD and subclinical atherosclerosis were included. The outcome data were extracted and pooled for the effect estimate by using a random‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 46 publications
1
55
1
5
Order By: Relevance
“…Strong evidence links NAFLD with objectively assessed subclinical atherosclerosis (including also increased coronary artery calcium score) in adults and adolescents, as well as with an increased prevalence of clinically manifest CVD both in the general population and in different patient groups [11,12,13]. Recently, in a large cohort of South Korean individuals without pre-existing CVD, Lee et al also showed that imaging-defined NAFLD was independently associated with a higher risk of having non-calcified, "vulnerable" coronary atherosclerotic plaques (as detected by coronary computed tomography angiography), thereby highlighting an increased NAFLD-related CVD risk among these asymptomatic individuals [14].…”
Section: Risk Of Cvd and Other Cardiac Complicationsmentioning
confidence: 99%
“…Strong evidence links NAFLD with objectively assessed subclinical atherosclerosis (including also increased coronary artery calcium score) in adults and adolescents, as well as with an increased prevalence of clinically manifest CVD both in the general population and in different patient groups [11,12,13]. Recently, in a large cohort of South Korean individuals without pre-existing CVD, Lee et al also showed that imaging-defined NAFLD was independently associated with a higher risk of having non-calcified, "vulnerable" coronary atherosclerotic plaques (as detected by coronary computed tomography angiography), thereby highlighting an increased NAFLD-related CVD risk among these asymptomatic individuals [14].…”
Section: Risk Of Cvd and Other Cardiac Complicationsmentioning
confidence: 99%
“…7 | 362-370 99 A plethora of studies report an association between NAFLD and these markers of preclinical atherosclerosis, with multiple systematic reviews and meta-analyses highlighting the association between NAFLD and carotid-artery intimamedia-thickness, coronary artery calcification and endothelial dysfunction, independent of traditional risk factors. [100][101][102][103] A recent systematic review and meta-analysis by Zhou et al 100 examining 26 observational studies further validated that the presence of NAFLD predisposes to a significantly higher risk of increased carotid artery intima-media thickness/plaques, arterial stiffness, coronary artery calcification and endothelial dysfunction, with odds ratios (95% confidence intervals) of 1.74 (1.47-2.06), 1.56 (1.24-1.96), 1.4 (1.22-1.60), and 3.73 (0.99-14.09) respectively. Casecontrol studies have also reported strong associations of NAFLD with early changes in left ventricular morphology and/or diastolic dysfunction with insulin resistance a likely key contributor.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…18,19 Amongst 7,196 individuals free of CVD, NAFLD presence and severity was associated with aortic stiffness beyond abdominal obesity 20 and with subclinical atherosclerosis; increased carotid artery intima-media thickness/plaques, arterial stiffness, coronary artery calcification, and endothelial dysfunction. 21 The presence and amount of steatosis was also recently related with impaired cardiac and autonomic function when compared with controls. 22 However, it is difficult to separate the effect of reduced insulin sensitivity from the direct effect of NAFLD on CVD risk.…”
Section: Does Improvement In Hepatic Fat Alter Cvd Risk?mentioning
confidence: 99%